Optimizing the efficiency of Oscillating Water Column (OWC) wave energy converter using genetic algorithm - Nallagownden, P. (Asian Research Publishing Network, 2015)
The Oscillating Water Column (OWC) based wave energy converter has now been developed in different part of the world. The OWC converter is a combination of pneumatic system, mechanical system and electrical system. The overall efficiency of OWC is depended on the three systems efficiencies. Maximizing each of these system efficiency can maximize the overall efficiency. This paper, describes a method to maximize the pneumatic system efficiency using optimization technique based on Genetic algorithm. This method involves an extraction of maximum incident wave energy corresponding to the wave height, determining of the best deep water length and maximizing the applied damping ratio which can lead to an increase in the pneumatic system efficiency. The result shows that the lower the number of the wave group, the maximum is the wave energy, that can be extracted and, optimum plane solidity and the water deep length can increase efficiency of OWC. Â© 2006-2015 Asian Research Publishing Network (ARPN).